59th Annual Meeting and 3rd World Congress on Exercise is Medicine of the American College of Sports Medicine (2012)
This conference reflects the College itself: richly diverse; rooted in tradition, yet innovative and forward-looking — and always based on the latest science and evidence. The 3rd World Congress on Exercise is Medicine offers attendees even broader programming, giving new tools to integrate Exercise is Medicine in practice and community. Top experts will discuss EIM topics ranging from geographical considerations, heath care integration, exercise in underserved populations, and more.